Analysis of the Relationship of Land Transportation with GDP Regional in the Construction Sector in Indonesia - Prasetyo, M. Ferdi; Setiawan, Muhammad Ikhsan; Dwi Apriliani, Dora; Prasetijo, Joewono (International Journal of Engineering, Science and Information Technology, 2023)
As the world's population increases, the need for a mode of transportation will increase, and the amount of transportation currently has positive and negative impacts. The positive impact is to help mobilize goods, people, and services. Negative impacts are traffic jams, air pollution, and accidents. This study aims to determine the relationship between land transportation and GDP Regional in the construction sector in Indonesia. The findings in this study indicate that (1) The relationship between GDP Regional for Construction and the length of State/National roads according to paved road surface has a deficient correlation level with a correlation interval value (0.105) with a Sig value (0.559 0.05). (2) The relationship between GDP Regional of construction and the length of provincial roads according to asphalt surface has a moderate relationship with a correlation interval value (0.527) with a Sig value (0.002 0.05), GDP Regional construction with a length of provincial roads according to gravel surface has a deficient relationship level with a correlation interval value (-0.271) with a Sig value (0.127 0.05).